Binhi towards a resilient urban food system through adaptable community food hubs - Te, Allison Denise L.
Food insecurity has been a chronic issue in the Philippines, which is further exacerbated by the increasing urbanization of the country, leading to limited resources, lack of space, and a degraded environment. Those most susceptible to the consequences of a fragile food system are marginalized populations often within the lower strata of society. As such, there is a need to reconfigure the food system into one that is more equitable and inclusive of these communities. Current attempts to alleviate these negative effects, however, fall short due to a number of reasons with one being the lack of proper channels to facilitate food programs, such as food distribution and skills development. The study then takes the opportunity to formalize the food hub typology within the local setting and veer from traditional production-centric food security programs. This is achieved by addressing the issues within the different dimensions of food security holistically through the integration of a food pantry, community kitchen, community garden, and other relevant programs. Moreover, the thesis aims to design for social and spatial adaptability to be able to reach marginalized communities in need of such programs and adjust to their varying circumstances. For the thesis, a site in Barangay Batis, San Juan City is used as a pilot model. Highlighting a community-based and transformative approach, the food hub becomes a conduit for social cohesion and community development as well, creating public and green spaces for said communities. In the end, the project becomes a model for decentralized and adaptable community food hubs that promote the distribution of food and food skills to vulnerable communities as a step towards a more resilient food system.